PEMBERDAYAAN KELOMPOK TANI BELIMBING PASIR PUTIH MELALUI PENYULUHAN PANGAN FUNGSIONAL KOMBUCHA CARAMBOLA BERBASIS GREEN ECONOMY UNTUK PENDERITA DIABETES MELITUS TIPE 2 - A'immatul Fauziyah; Anastasia Bernadin; Vina Mahdalena; Sintha Fransiske S; Lusia Handayani; Dhiya Agis Ghazalah; Olivia Nadine; Ralitsa Putri Alfasari (Jurnal Abdi Insani, 2026)
This community empowerment activity was motivated by the high prevalence of Type 2 Diabetes Mellitus (DMT2) in Pasir Putih, Depok which reached 54,4%, along with the low income of starfruit farmers due to limited product innovation. These interwined health and economics issues required a community-based solution through the development of functional foods utilizing local agricultural products. Education on DMT2 and the processing of starfruit into kombucha carambola based on the green economy concept aimed to increas farmers knowledge while promoting sustainable economic independence. The purpose of this activity was to enhance the knowledge of the starfruit farmers group regarding DMT2, functional food, and the green economy concept to help reduce DMT2 prevalence and improve community welfare. The activity employed a participatory approach through counseling and training involving a8 participants from the Pasir Putih starfruit farmers group. Evaluation was conducted using pretest and post-test analyses with descriptive statistics and a Paired Sample T-Test. The result showed an increase in the average knowledge score from 9,28 to 10,22 after the counseling session with a significance value of P=0,009 (P<0,05). This indicates that the educational intervention effectively improved farmers unferstanding of DMT2, functional food, and the green economy concept. Morover, the activity encouraged farmers to develop environmentally friendly starfruit-based product with higher market value. The counseling program significanly improved farmers knowledge and has potential to support DMT2 control and sustainable local economic growth.